Combustion Characteristics and Cyclic Variation of a LPG Fuelled MPFI Four Cylinder Gasoline Engine. (December 2016) - Nayak, Vighnesha; Rashmi, G.S.; Chitragar, Parashuram; Mohanan, P.
Abstract: Present study deals with to investigate the effect of dual mode of operation on combustion characteristics of engine and cyclic variation in a modified multi-cylinder SI engine. Experiments will be conducted with baseline gasoline and later with dual fuel mode of experiments i.e., gasoline with LPG with different ratios (25%, 50%, 75% and 100% of LPG by mass). Experiment will be carried out with varying speed from 2000 rpm to 4500 rpm in steps of 500 rpm at full load condition with factory set static ignition timing of 5 deg. bTDC to investigate combustion characteristics and cyclic variations. Results revealed that as the LPG percentage increases the peak pressure also increases and it is maximum for 100% LPG for all the speed. At 4500 rpm the percentage increase in peak pressure is 20% for 100% LPG, 9% for 25%LPG, 3% for 50%LPG, 1% for 75%LPG when compared to gasoline at full load. This increase in peak pressure will indicate the LPG will give better combustion properties compared to that of gasoline. Compared to peak pressure, the variation in cycle to cycle for IMEP is less.Net heart release rate shows that gasoline will give the more heat release compare to all other fuels, but LPG will release the heat little earlier than gasoline. Since peak pressure is near to TDC for LPG which results in NHRR to occur earlier than gasoline. Final outcome of the research is LPG will have better combustion properties compared to gasoline but cyclic fluctuations are more for LPG.